Applying the EU Green Taxonomy Principles in Order to Preserve Biodiversity, In Particular Wild Sturgeon Populations - György Deák; Matei Stelian; Sadîca Isabela; Monica M.; Mădălina Boboc; Laslo Lucian; Holban Elena; Cucu George (E3S Web of Conferences)
The three wild anadromous sturgeon species currently present in the Black Sea and Lower Danube are in a critically endangered state. Their population has been consistently declining due to a combination of various factors, both caused by human activity and natural phenomena. These factors include unsustainable exploitation and poaching, hydro-technical projects aimed at improving navigation, water management, and energy production, pollution of essential habitats, and climate change. The EU Green Taxonomy is an essential framework that facilitates collaboration between researchers, communities, and the government to protect natural ecosystems and conserve biodiversity while promoting a sustainable and balanced socioeconomic environment. INCDPM Bucharest has developed a research agenda for environmental protection and biodiversity conservation based on the six main principles of the Green Taxonomy. This agenda focuses on 7 core themes that address the highest priorities in these areas and provide future scientific directions to achieve these goals.